The impact of training courses on the skills of the graphic designer from the point of view of graphic designers in the State of Kuwait - Abaalkhail, Mona Marmah (Journal of Educational and Psychological Sciences, 2022)
This study aimed to reveal the impact of training courses on the skills of the graphic designer, and in order to achieve the goal of the study, the descriptive analytical method was used. A questionnaire was developed and distributed to a sample of (224) designers working in the State of Kuwait. The results of the study showed that the means of the degree to which graphic designers in the State of Kuwait possess graphic design skills was (3.44 out of 5), at a (medium) degree. Also, the means of the training courses level was (3.40), at a (medium) degree. There is also a statistically significant effect at the significance level (α≤0.05) and that the most influential dimensions in the graphic designer’s skills were (activities) with a value of Beta (0.44), followed by the (training material) with a value of Beta (0.22), and finally (the trainer), with a value of Beta (0.13), and reflects an effect (large / medium). The results of the study indicated that there were statistically significant differences in the study sample’s estimations towards training courses due to the variable (gender) and in favor of males, and the results showed the absence of statistically significant differences in the study sample’s estimations towards training courses due to the variable (experience).In light of the results reached, the researcher recommended the necessity of holding courses and workshops in order to develop and develop the skills of the graphic designer in the State of Kuwait in line with the requirements of the stage, especially with regard to the use of the skills of imagination and creativity in design.